Zero grazing in Kenya - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Increased agricultural output from a smaller land area is the challenge facing all countries with rapidly rising populations. In Kenya, to meet the growing demand for dairy products, milk production has to double in a period of less than 15 years....